Modeling of 2-DOF Hexapod Leg Using Analytical Method - Wajiansyah, Agusma; Supriadi, Supriadi; Gaffar, Achmad Fanany Onnilita; Putra, Arief Bramanto Wicaksono (Journal of Robotics and Control (JRC), 2021)
Walking robot is one type of mobile platform that has locomotion type "walking." DOF (Degree Of Freedom) is one of essential character for the design of robot mechanism based on its models. Legs are the critical parts of the walking robot structure. The legged robot is the walking robot biologically adopted from animal or insect behavior, especially in their walking routine. The hexapod robot is one of the most statically stable legged robots and has high flexibility when standing or moving which supported by six legs that can be easily manipulated. For modeling needs and its validation, it is desirable to control each DOF in the space of Cartesian coordinate although motor system needs the reference inputs in the joint space. In this case, it needs to know the conversion between Cartesian and joint space, inverse, and forward kinematics. This study presents a kinematic model of the 2-DOF hexapod leg. This study aimed to build a kinematic model of the 2-DOF hexapod leg using an analytical approach. Analytically, the working mechanism of the robot can be modeled using forward and inverse kinematic models. In this method, this modeling is derived mathematically from the projection analysis of the movement in a certain coordinate space. The model validation was performed using the MATLAB tool and the Robotic Toolbox. The results of this study showed that the results of the inverse kinematic process have the same output signal pattern compare to the input signal pattern of the forward kinematic process.